Laparoscopic‐endoscopic cooperative surgery for ileal lipoma: A case report. Issue 2 (11th April 2019) - Nakanishi, Ryota; Fukunaga, Yosuke; Nagasaki, Toshiya; Emoto, Shin; Hirayama, Kazuyoshi; Yoshioka, Satoshi; Kitagawa, Yusuke; Honma, Satoru; Nagaoka, Tomoyuki; Matsui, Shimpei; Tominaga, Tetsuro; Minami, Hironori; et al.
Abstract: This is the first report of laparoscopic‐endoscopic cooperative surgery (LECS) for an ileal tumor. A 50‐year‐old man was admitted to our hospital with a positive fecal occult blood test. Colonoscopy detected a submucosal tumor with intussusception located in the ileum, 10 cm oral from the Bauhin valve. On further examination, he was diagnosed with an ileal lipoma. There were no signs of malignancy. LECS was performed for the ileal tumor. After submucosal elevation by injecting saline solution, a mucosal incision was made circumferentially along the tumor. A full‐thickness incision was created endoscopically and laparoscopically on the circumferential mucosal incisional line. The tumor was withdrawn intraluminally by endoscopy. The defect of the ileal wall was closed laparoscopically in an axial direction with linear staplers. Histologically, the tumor was a 25‐mm ileal lipoma with negative resection margins and no malignancy.